Outstanding Photo-bioelectrochemical Cell by Integrating TiO2 and Chlorophyll as Photo-bioanode for Sustainable Energy Generation - Marcelinus Christwardana; Athanasia Amanda Septevani; Linda Aliffia Yoshi (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Photosynthesis is a technique for converting light energy into chemical energy that is both efficient and sustainable. Chlorophyll in energy-transducing photosynthetic organisms is unique because of their distinctive structure and composition. In photo-bioelectrochemical research, the chlorophyll's quantum trapping efficiency is attractive. Chlorophyll from Spirulina platensis is demonstrated to communicate directly with TiO2-modified Indium Thin Oxide (ITO) to generate electricity without the use of any mediator. TiO2-modified ITO with a chlorophyll concentration of 100 % generated the greatest power density and photocurrent of approximately 178.15 mW/m2 and 596.92 mA/m2 from water oxidation under light among all the other materials. While the sensitivity with light was 0.885 mA/m2.lux, and Jmax value was 1085 mA/m2. Furthermore, the power and photocurrent density as a function of chlorophyll content are studied. The polarizability and Van der Waals interaction of TiO2 and chlorophyll are crucial in enhancing electron transport in photo-bioelectrochemical systems. As a result, this anode structure has the potential to be improved and used to generate even more energy.